PENGARUH PESAN KOMUNIKASI PADA KEMASAN ROKOK TERHADAP SIKAP PEROKOK MUDA DI KOTA SURABAYA - Ana R, Adelina Erlinda; Bungin, Burhan; Novaria, Rachmawati (representamen, 2018)
Health warning labels on cigarette packs is very important as a means of communication andawareness of smokers of the health risks caused by smoking. By reading and seeing pictures of healthwarnings, with some warning messages of health and some disease the effects of smoking are listed onthe label of health warnings on cigarette packs every time they smoke, is expected to provide a greaterknowledge of the health effects of smoking, and may raise intention to quit smoking and thereforecontributes to the attitude of smokers. The purpose of this study was to determine the effect ofcommunication messages on pictorial health warning labels on cigarette packs on the attitudes ofyoung smokers in the city of Surabaya. The minimum sample empirically determined as much as 96respondents using accidental sampling technique. Results of research and analysis with a simplelinear regression showed that a significant difference between the message communication onpictorial health warning labels on cigarette packs on the attitudes among young smokers in the city ofSurabaya. Contributions message communication on pictorial health warning labels on cigarettepacks on the attitudes of young smokers in the city of Surabaya is 47.6% of the remaining 52.4% isinfluenced by other variables not examined in this study, for example the influence of friends, lifestyle,etc.Keywords: communication messages, the attitude of young smokers